Analysis of the rules of documentary evidence in the case of PP v Dato’ Sri Mohd Najib Hj Abd Razak - Ngau, Hwa Wei (Fakulti Undang-Undang, Universiti Kebangsaan Malaysia, 2021)
It is undoubted that the role of the law of evidence is indispensable part of the criminal trial. The technicality issue of the admissibility of evidence is always deemed as the paramount axis and decisive factor of the criminal case for both the prosecution and the defence in proving their case. Recently, the application of the documentary evidence has been highlighted by the court in the highly attaching case of the PP v Dato’ Sri Mohd Najib Hj Abd Razak. In this case, the argument around the law of evidence regulating the documentary evidence is put forward as the hot topic. The detail discussion on the relevant rules and law has been assessed by the trial court carefully and comprehensively in its judgement in resolving the legal issues and clarifying the debate casted by both the learned prosecutor and defence counsel. The analysis of the latest established rules of evidence concerning the documentary evidence have be pointed out and reflected by referring to the judgement of the case of PP v Dato’ Sri Mohd Najib Hj Abd Razak. The analysis is made on the stages of the general discussion of the rule of relevancy and admissibility of the documentary evidence, the new or alternative approach in interpreting the rules of documentary evidence and the available exception to its general rule of admissibility. The findings of this paper showed that despite that the best evidence rule is the primary precept of the admissibility of the documentary evidence, but its application is not conclusive as it is always subjected to the other principles of the law evidence especially when it is involved the admissibility of the electronic documentary evidence.